Cauliflowers or how the perseverance of a plant to make flowers produces an amazing fractal structure - Azpeitia, Eugenio; Parcy, François; Godin, Christophe (Comptes Rendus Biologies, 2023)
Biological organisms have an immense diversity of forms. Some of them exhibit conspicuous and fascinating fractal structures that present self-similar patterns at all scales. How such structures are produced by biological processes is intriguing. In a recent publication, we used a multi-scale modelling approach to understand how gene activity can produce macroscopic cauliflower curds. Our work provides a plausible explanation for the appearance of fractal-like structures in plants, linking gene activity with development.